2022
DOI: 10.1039/d1qm01540k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of broadband NIR garnet phosphor Ca4ZrGe3O12: Cr3+, Yb3+ for NIR pc-LED applications

Abstract: Near-infrared phosphor-converted light-emitting diodes (NIR pc-LEDs) have outstanding application prospects in many fields such as non-destructive detection, bioimaging and modern agriculture, in which the development of NIR emitting phosphor with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 33 publications
0
53
0
Order By: Relevance
“…Considering both the results of low-temperature tests and the valence and radius of the ions, we deduced that it is easier for Cr 3+ ions to enter the Sc 3+ octahedral lattice. 17,18…”
Section: Results and Analysismentioning
confidence: 99%
“…Considering both the results of low-temperature tests and the valence and radius of the ions, we deduced that it is easier for Cr 3+ ions to enter the Sc 3+ octahedral lattice. 17,18…”
Section: Results and Analysismentioning
confidence: 99%
“…21 Furthermore, the thermal resistance, luminous efficiency, and FWHM of some Cr 3+ activated phosphors can be improved by Yb 3+ co-doping. 22–25 Xu et al reported a highly efficient (IQE = 77%) LiInSi 2 O 6 :Cr 3+ phosphor with NIR emissions peaking at 840 nm, and the prepared pc-LED had an excellent NIR output power (51.6 mW@100 mA). 26 Liu et al improved the optical properties of the LiIn 2 SbO 6 :Cr 3+ phosphor by Zn 2+ co-doping.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the low IQY of LiScP 2 O 7 :Cr 3+ is also less than satisfactory. Xiang et al reported a broadband NIR phosphor Ca 4 ZrGe 3 O 12 :Cr 3+ ,Yb 3+ that also shows that the thermostability can be improved by codoping Cr 3+ and Yb 3+ ions . Therefore, novel materials that provide crystallographic sites for Cr 3+ and Yb 3+ ions may be beneficial for obtaining NIR broadband emissions with much larger fwhm, better thermostability, and higher IQEs.…”
Section: Introductionmentioning
confidence: 99%
“…25 However, the low thermal stability and internal quantum efficiency (IQY) limit its application in NIR pc- 3+ that also shows that the thermostability can be improved by codoping Cr 3+ and Yb 3+ ions. 26 Therefore, novel materials that provide crystallographic sites for Cr 3+ and Yb 3+ ions may be beneficial for obtaining NIR broadband emissions with much larger fwhm, better thermostability, and higher IQEs. Furthermore, the emission intensity of Cr 3+ also suffers from the concentration quenching effect.…”
Section: ■ Introductionmentioning
confidence: 99%